2021
DOI: 10.3390/nu13061916
|View full text |Cite
|
Sign up to set email alerts
|

The Speed of Ingestion of a Sugary Beverage Has an Effect on the Acute Metabolic Response to Fructose

Abstract: Background: The consumption of sweetened beverages is associated with increased risk of metabolic syndrome, cardiovascular disease, and type 2 diabetes mellitus. Objective: We hypothesized that the metabolic effects of fructose in sugary beverages might be modulated by the speed of ingestion in addition to the overall amount. Design: Thirty healthy subjects free of any disease and medication were recruited into two groups. After overnight fasting, subjects in group 1 drank 500 mL of apple juice over an hour by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 54 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…Thus, mice lacking fructokinase show an impaired vasopressin response to dehydration [ 104 ]. Moreover, the oral ingestion of fructose in both laboratory animals [ 60 , 64 , 106 ] and humans [ 105 , 107 ] results in a rise in vasopressin (copeptin) levels in the blood. Thus, fructose metabolism is directly linked with the stimulation of the vasopressin system ( Figure 1 ).…”
Section: Metabolic Cardiovascular and Renal Effects Resulting From Po...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, mice lacking fructokinase show an impaired vasopressin response to dehydration [ 104 ]. Moreover, the oral ingestion of fructose in both laboratory animals [ 60 , 64 , 106 ] and humans [ 105 , 107 ] results in a rise in vasopressin (copeptin) levels in the blood. Thus, fructose metabolism is directly linked with the stimulation of the vasopressin system ( Figure 1 ).…”
Section: Metabolic Cardiovascular and Renal Effects Resulting From Po...mentioning
confidence: 99%
“…In this regard, we have found that a high salt diet (or dehydration itself) can induce both fructose and vasopressin formation [ 64 , 104 , 107 ]. Moreover, high salt intake may lead to increases in serum osmolality, thereby inducing chronic underhydration, activating both the polyol-fructose and vasopressin pathways.…”
Section: Metabolic Cardiovascular and Renal Effects Resulting From Po...mentioning
confidence: 99%
“…Overall, the cFGF21 concentration was significantly higher in individuals with different diets (SMD=1.03 pg/ml, 95%CI: 0.28-1.78, p=0.007) (Experimental) compared to their cFGF21 levels before indicated diet interventions (Control), largely contributed by the significant elevation of cFGF21 in individuals with a hypercaloric carbohydrate-rich diet ( 15 ) (p=0.01), hypercaloric fat-rich diet ( 16 18 ) (p=0.01), amino acid- or protein-restricted diets ( 19 23 ) (p=0.02) and fructose intake ( 24 , 25 ) (p<0.0001) ( Figure 3 ). While a quick and excessive drink of apple juice significantly increased the cFGF21 level, the overall effect of apple juice consumption on the cFGF21 level was insignificant ( 26 ) (p=0.06), due to a nonsignificant increase in cFGF21 after a slow drink of apple juice. Only consuming fish oil significantly downregulated the cFGF21 concentration ( 27 ) (p<0.00001) without affecting the overall effects of diets on the cFGF21 concentration (p=0.007).…”
Section: Resultsmentioning
confidence: 90%
“…Increases serum osmolarity by shifting fluid to intracellular compartment (in rats) [34] Stimulates vasopressin production via osmolar and nonosmolar pathways [35] Oral fructose increases serum vasopressin (copeptin) in humans [36] Stimulates foraging responses…”
Section: Stimulates Hungermentioning
confidence: 99%
“…The most compelling evidence of beneficial effects of the loss of uricase are related to the ability of fructose to aid survival (Table 2) [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. As mentioned, the main nutrient of ancestral apes was fruit, which is rich in fructose.…”
Section: Benefits Of the Uricase Mutation In Circumstances Of Seasona...mentioning
confidence: 99%